Estimasi Emisi Metana (Ch4) Di Tempat Pembuangan Akhir Kota Pekanbaru Menggunakan Dispersi Aermod - Dinda Lestari; Fitri, Yulia; Rahmadani, Nofia; Mulyani, Sri; Retnawaty, 2Sri Fitria; Selvia (Jurnal Permukiman, 2024)
Methane gas is one of the greenhouse gases that is 21 times more potent than C02. Therefore, it is necessary to estimate the quality of pollutants released by landfills around the world. The purpose of this research is to predict the amount of methane emitted from Muara Fajar 2 landfill in Pekanbaru city using Landfill Gas Emissions (LandGEM) model. AERMOD is used to model the distribution of pollutants generated by landfills. This model requires meteorological data such as temperature, temperature, wind direction, wind speed, radiation, air pressure, cloud cover, humidity and cloud base height. The meteorological parameters used in this study are meteorological data obtained from the Climate Data Store (CDS) of Pekanbaru city. The results showed that the peak of methane emissions produced by Muara Fajar 2 Landfill was 19,290 Mg/year in 2049. Pollutant dispersion showed that in 2022 Muara Fajar 2 Landfill produced a dispersion of 2447814 μg/m3. Methane gas pollutants produced by Muara Fajar 2 Landfill have no impact on the surrounding environment.